Transradial access for balloon-assisted maturation of arteriovenous fistulas - Mayumi Kohiyama, BS; Tabea Hoffstaetter, BS; Jeffrey Silpe, MD, MS-HPEd; Avinash Garlapati, BS; Gregg S. Landis, MD; Yana Etkin, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
Balloon-assisted maturation (BAM) of arteriovenous fistulas has conventionally been performed via direct fistula access. The transradial approach has not been well described for BAM, although its use has been reported throughout the cardiology literature. The purpose of the present study was to assess the outcomes of transradial access for its use with BAM. A retrospective review of 205 patients with transradial access for BAM was performed. One sheath was inserted into the radial artery distal to the anastomosis. We have described the procedural details, complications, and outcomes. The procedure was considered technically successful if transradial access had been established and the AVF had been ballooned with at least one balloon without major complications. The procedure was considered clinically successful if no further interventions had been required for AVF maturation. The average time for BAM via transradial access was 35 ± 20 minutes, with 31 ± 17 mL of contrast used. No access-related perioperative complications, including access site hematoma, symptomatic radial artery occlusion, or fistula thrombosis, had occurred. The technical success rate was 100%, and the rate of clinical success was 78%, with 45 patients requiring additional procedures to achieve maturation. Transradial access is an efficient alternative to trans-fistula access for BAM. It is technically easier and allows for better visualization of the anastomosis.